Predicting the uptake of Cs, Co, Ni, Eu, Th and U on argillaceous rocks using sorption models for illite. (August 2015) - Marques Fernandes, Maria; Vér, Nóra; Baeyens, Bart
Highlights: Contaminant retention in argillaceous rocks controlled by sorption on clay minerals. Cs, Ni, Co, Eu, Th and UO2 sorption isotherm measurements on Boda and Opalinus Clay. Boda and Opalinus Clay exhibit different mineralogies and porewater compositions. Blind predictions using quasi-mechanistic sorption models developed for illite. Good agreement between measurements and blind predictions. Abstract: Reliable predictions of radiocontaminant migration are a requirement for the establishment of radioactive waste repositories. Parametrization of the necessary sorption models seems to be, however, extremely challenging given the multi-mineralic composition of the lithosphere. In this study it is shown for two argillaceous rocks – Boda and Opalinus Clay relevant for the Hungarian and Swiss repository concepts, respectively – that this task can be substantially simplified by taking into account only the most sorptive mineral fraction, namely the 2:1 clay minerals illite and illite/smectite mixed layers. Two different models were required to blind predict the sorption isotherms of Cs, Co, Ni, Eu, Th and UO2 measured on the two clay rock samples in a synthetic porewater. Cs sorption was modelled with theg eneralisedCs (GCs) sorption model and the sorption of the other cations with the2 s itep rotolysisn one lectrostatics urfacec omplexation andc atione xchange (2SPNE SC/CE) model. The 2SPNE SC/CE model for illite was extended with surface complexation reactions on weak sites for Co, Ni, Eu, UO2 and on strong sites for Eu-carbonato complexes. Complementary to the sorption measurements and modelling, extended X-ray absorption fine structure (EXAFS) spectroscopy was used to probe the retention mechanism of Ni on illite, Boda and Opalinus Clay at higher loadings. The reliable blind predictions of the selected metal cations, which are representative for monovalent alkaline metals, divalent transition metals, lanthanides, and trivalent, tetravalent and hexavalent actinides, confirms the applicability of this simplified bottom up approach, and, renders the underlying sorption models particularly useful to predict sorption for the wide range of cations to be considered in the safety analysis of radioactive waste repositories in clay-rich environments.